Evaluation of spread-out perceivedness effectiveness tree-branch shape on the foliage via changing-status method: Correlation with rectangular-shape-structur - Kim, Jeong-Lae; Cho, Kyung-Seu (Edelweiss Applied Science and Technology, 2025)
Flowers come in a variety of shapes and colors and are composed of different types of reproductive organs and pedicels. At the tip of the flower’s reproductive axis, small sporophylls and large sporophylls are attached, and the tip of the peduncle has various shapes and colors, each characterized by different plant species. Flowers with various winding structures have a rectangular structure, which is an important factor in the engineering of winding structures. The forming model of foliage that can estimate symmetry is the tree-branch shape, which is transformed into a scalelike-wave-like-branch-dot of a one-branch tree along the fractal line on the surface by using the spread-out-shaking method. Foliage spread-out perceived imagery is a foliage spread-out shaking imagery that organizes the one-branch tree state into a foliage spread-out perceived imagery by glaring perceivedness rate (GPR) and differentiation perceivedness rate (DPR) shown in a scalelike-wave-like-branch-dot pattern. The spread-out changing-status technique organizes the perceivedness rate condition to be used in the waft shaking system. As a result of tree-branch shaping far changing-status, the spread-out value of Spo-pi-FA-ΨMED-MIN was 4.32±(-0.14), the spread-out value of Spo-pi-CO-ΨMED-MIN in convenient changing-status was 1.81±0.16, and the spread-out value of Spo-pi-FL-ΨMED-MIN in flank changing-status was 10.35±0.07. The spread-out value of Spo-pi-FL-ΨMED-MIN in the flank changing-status was 1.29±0.32, and the spread-out value of Spo-pi-VI-ΨMED-MIN in the purlieus changing-status was 0.06±(-0.01). The rectangular-shape structure with tree-branch shape is a perceivedness rate system that improves the ability of foliage spread-out-shaking imagery, and the rectangular-shape degree perceivedness rate of GPR-DPR occurs and constitutes glaring and differentiation imagery. Perceivedness imagery in tree-branch shape will be able to detect the imagery by differentiation signal and utilize the waft perceivedness system to mathematically model the spread-out data of winding structures.